INTERACTIVE LEARNING MEDIA INNOVATION TO IMPROVE DIGITAL ERA LEARNING AT MTSN 3 ABDYA SCHOOL - Yayang Fazila. R; Sukri Adani (Yayasan Nusantara Hasana Berdikari, 2025)
Technological advances bring profound changes in the learning paradigm, encouraging the use of innovative and interactive learning media to improve the effectiveness of learning amidst the challenges of the times. Education must adapt to these changes, to meet the demands of a digital society that increasingly relies on technology. This study aims to develop innovations in interactive learning media to Improve Digital Era Learning at Mtsn 3 Abdya School. This learning media was developed using teaching materials equipped with interactive features such as videos, animations, and quizzes. This study is based on a literature study research approach to investigate innovation in the development of interactive learning media in order to improve the effectiveness of learning in the digital era. The results of this research show that interactive learning media innovation has made a positive contribution to increasing the effectiveness of learning at the MTsN 3 ABDYA school.